2022
DOI: 10.1097/pcc.0000000000002969
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B Hemoperfusion in Pediatric Septic Shock: Single-Center Observational Case Series

Abstract: OBJECTIVES: To evaluate the use of direct hemoperfusion with polymyxin B-immobilized fiber (PMX-DHP) as adjunctive therapy during pediatric patients with septic shock. DESIGN: Prospective observational study. SETTING: Nine-bed PICUs at university referral hospital. PATIENTS: Children (30 d to 15 yr) with septic shock and Pediatric Logistic Organ Dysfunction (PELOD)-2 score greater than or equal to 10 or Pediatric Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hemoperfusion can be performed in severe COVID-19 patients with cytokine release syndrome, particularly when contemplating ECMO support. Some case studies have reported swift reductions in vasopressor demand, rapid hemodynamic stabilization, decreases in IL-6 levels, enhancements in chest X-rays, and improvements in acute kidney injury outcomes [39]. However, as mentioned earlier in the randomized study [36], the use of Cytosorb® hemoperfusion during ECMO support did not result in reduced IL-6 concentrations.…”
Section: Severe Covid-19mentioning
confidence: 86%
See 1 more Smart Citation
“…Hemoperfusion can be performed in severe COVID-19 patients with cytokine release syndrome, particularly when contemplating ECMO support. Some case studies have reported swift reductions in vasopressor demand, rapid hemodynamic stabilization, decreases in IL-6 levels, enhancements in chest X-rays, and improvements in acute kidney injury outcomes [39]. However, as mentioned earlier in the randomized study [36], the use of Cytosorb® hemoperfusion during ECMO support did not result in reduced IL-6 concentrations.…”
Section: Severe Covid-19mentioning
confidence: 86%
“…Notably, a recent prospective observational case series explored the use of adjunctive polymyxin B hemoperfusion in children with refractory septic shock. After undergoing two hemoper- fusion sessions, clinical hemodynamics improved significantly, along with reductions in severity of illness scores, and importantly, no device-related adverse events were recorded [39].…”
Section: Conditions With Uncontrolled Cytokine Release (Cytokine Storm)mentioning
confidence: 92%
“…Polymyxin-B hemoadsorption with PMX-05 cartridges was applied in 15 children with septic shock; the authors reported a trend towards an improvement in hemodynamics after two sessions of therapy, although inotropic agent requirements did not change over time ( 32 ). More recently, Saetang et al described the use of PMX-20R (a modified polymyxin-B cartridge circuit for pediatric use) in 6 children and reported a significant reduction in PELOD-2 and VIS scores after two sessions of therapy ( 33 ). Clinical experiences are also reported on application of the Selective Cytopheretic Device (SCD) in critically ill children with AKI and multiorgan dysfunction showing promising results in terms of safety and efficacy ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential benefits of RRT in sepsis include the treatment of fluid overload and metabolic disturbances unresponsive to medications, but RRT is not associated with other PICU outcomes [37]. The potential benefits of blood purification in sepsis encompass the reduction of various pro-inflammatory cytokines levels (IL-1β, IL-6, IL-8, and TNF-α), a decreased vasopressor-inotropic score (VIS), a lowered Pediatric Logistic Organ Dysfunction (PELOD-2) score at 72 hours, a shortened ICU length of stay, and a reduced mechanical ventilator day [38][39][40][41][42]. Different adsorptive columns exhibit varying reported benefits, though specific details for each adsorptive column are not fully described for simplicity of recommendation.…”
Section: Renal Replacement Therapy and Extracorporeal Blood Pu-rifica...mentioning
confidence: 99%